2013
DOI: 10.1175/jhm-d-12-083.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall in the Mediterranean: What Can We Learn from Observations?

Abstract: Flash floods induced by extreme rainfall events represent one of the most life-threatening phenomena in the Mediterranean. While their catastrophic ground effects are well documented by postevent surveys, the extreme rainfall events that generate them are still difficult to observe properly. Being able to collect observations of such events will help scientists to better understand and model these phenomena. The recent flash floods that hit the Liguria region (Italy) between the end of October and beginning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 31 publications
2
104
0
Order By: Relevance
“…Due to self-regenerating storm cells or to persistent cyclonic Tyrrhenian circulation (Crosta 1998;Cevasco et al 2009), extreme precipitation can occur, between late summer and mid-autumn, along the coast of eastern Liguria (van Delden 2001;Silvestro et al 2012Silvestro et al , 2015Rebora et al 2013;Buzzi et al 2014;Cevasco et al 2015;Cassola et al 2016). Usually these rainstorms have short duration (<24 h), but rainfall intensities can reach or exceed values of 100 mm h ¡1 .…”
Section: General Features Of the Study Areamentioning
confidence: 99%
“…Due to self-regenerating storm cells or to persistent cyclonic Tyrrhenian circulation (Crosta 1998;Cevasco et al 2009), extreme precipitation can occur, between late summer and mid-autumn, along the coast of eastern Liguria (van Delden 2001;Silvestro et al 2012Silvestro et al , 2015Rebora et al 2013;Buzzi et al 2014;Cevasco et al 2015;Cassola et al 2016). Usually these rainstorms have short duration (<24 h), but rainfall intensities can reach or exceed values of 100 mm h ¡1 .…”
Section: General Features Of the Study Areamentioning
confidence: 99%
“…From a meteorological point of view, the 25OCT2011 rainfall event was deeply investigated by Buzzi et al (2014) using a numerical weather model and by Rebora et al (2013) using the measurements available from a large number of sensors, both ground based and space borne. In this latter paper, the authors concluded that the large-scale features of the event and the complex geographical characteristics of the area determined the conditions for the persistence of heavy precipitations over the same region, i.e.…”
Section: Study Case 25 October 2011mentioning
confidence: 99%
“…In recent years, Tuscany region and nearby areas (central Italy), have been hit by noticeably heavy rainfall events (Parodi et al, 2012;Sacchi, 2012;Avanzi et al, 2013;Rebora et al, 2013;Fiori et al, 2014;Buzzi et al, 2014;Perna et al, 2015). In particular the northwestern part of the Tuscany region is very prone to frequent and severe rainstorms, due to its geographical position and its steep orography close to the sea, making this area one of the wettest in northern and central Italy (Brunetti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within small and densely urbanized areas, intensive and stationary precipitation events can rapidly result in dangerous floods, sometimes leading to disastrous consequences (e.g. Silvestro et al, 2012;Rebora et al, 2013;. This stresses the importance of such events through their impacts on the social and economic circumstances of local communities.…”
Section: Introductionmentioning
confidence: 99%